FEASIBILITY OF EDUCATIONAL MEDIA FOR THE DEVELOPMENT OF TODDLERS WITH MONOPOLY GAME - Wanodya Hapsari; Hesti Kurniasih; Puji Hastuti (Universitas Karya Husada Semarang, 2025)
This research was carried out on stimulation, detection and early intervention education for the development of toddlers with monopoly game media. Aims to provide knowledge about developmental disorders early. One of the efforts to optimize children's health services is through initial screening for growth and development disorders and is carried out in a coordinated manner in the form of partnerships between parents, caregivers, other family members, cadres, professional organizations, non-governmental organizations and health workers. Various media have been used in providing education, including whatsapp groups, sensory play kits, android-based toddler growth and development care, modules, simulation games, booklets, leaflets, but there are still children who experience growth and development disorders. The sample in this study was parents in the Baturraden sub-district area of Banyumas Regency as many as 30 people, using incidental sampling. This research is research and development, referring to the Instructional Design research and development model with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. Validation of material experts is carried out by pediatricians, health promotion lecturers and health center midwives. Product implementation is parents of toddlers. Conclusion: educational media for stimulation, detection and early intervention of toddler development with monopoly game media was declared feasible by experts.